Effects of hands-on instructional strategy on senior school students’ performance in waves - Abdulrasaq Oladimeji Akanbi; Ridwan Enuwa Mohammed; Aishat Abdulqadir Yusuf; Yahaya Wasiu Olayinka (Intelektual Pustaka Media Utama, 2022)
The research examined the effects of hands-on teaching strategy on senior school learners’ performance waves in Ilorin, Nigeria. Senior secondary school (SSS2) science students were sampled at intact classes using a purposive sampling technique. Researcher-designed instructional packages on waves and Physics achievement test on waves (PATW) were the instruments employed. The gathered data were analysed with the use of descriptive and inferential statistics. Percentage, mean and standard deviation were employed in answering the research question. Meanwhile, Analysis of Variance (ANOVA) was utilised in testing the hypotheses formulated at a 0.05 alpha level. The study showed that students’ performance exposed to hands-on instructional strategy was very impressive, while students’ performance exposed to traditional strategy was low, there was a significant effect of hands-on instructional technique on the performance of students in waves and no statistically significant collaborative effect of hands-on instructional technique and students’ gender on performance in waves. It was suggested that hands-on instructional strategies should be integrated and used to make teaching and learning more concrete and active based for both teachers and students.